DNA Barcoding Reveals High Hidden Species Diversity of Chinese Waters in the Cephalopoda - Xu, Ran; Lü, Yuhan; Tang, Yan; Chen, Zhiwei; Xu, Chenxi; Zhang, Xiaoying; Zheng, Xiaodong (Frontiers in Marine Science, 2022)
Species delimitation by traditional morphological methods is challenging in cephalopods due to their flexible bodies, changeable pigment traits, and sometimes high morphological homoplasy. Molecular information provides important assistance for the taxonomic decision. In this study, we applied three species delimitation methods on 132 cephalopods from 7 families along Chinese waters, and we found underestimated species diversity in these taxa. A maximum of 56 molecular operational taxonomic units (MOTUs) was detected, and possible cryptic diversities were revealed in Loliolus beka, Uroteuthis edulis, Octopus minor, Amphioctopus fangsiao and Hapalochlaena lunulate. This study provides molecular evidence for the hidden species diversity along the Chinese water, and it provides insight into further taxonomic research on these morphologically variable taxa.